Transformation of Local Wisdom as a Learning Resource for Environmental Education in Elementary Schools Through an Ethnopedagogical Approach - Sukirno; Sriyanto (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2026)
The transformation of local wisdom into a learning resource for environmental education is becoming increasingly urgent because environmental learning in elementary schools remains largely theoretical and insufficiently connected to students’ socio-cultural realities. As a result, students often fail to relate environmental concepts to their daily lives and local contexts. This study analyzes how ecological values embedded in Ajibarang's local culture, particularly the prohibition against cutting trees on Mount Krikil and the belief in the sacredness of the Kali Manggeng water, are conceptually transformed into environmental learning through an ethnopedagogical approach. A qualitative method with an educational ethnography design was employed to collect data through in-depth interviews, observations, and documentation involving school principals, teachers, and community leaders. The findings reveal that Ajibarang’s local culture embodies strong values of conservation, ecological ethics, and environmental spirituality that guide community behavior. Schools have begun to develop initial frameworks for integrating these values into classroom learning, school culture, and the Pancasila Student Profile Project. Teachers and community leaders serve as cultural mediators, translating local beliefs, narratives, and practices into meaningful learning activities. The study concludes that local wisdom holds strong potential as a foundation for more contextual, meaningful, and relevant environmental learning.